2014
DOI: 10.1093/eurpub/cku117
|View full text |Cite
|
Sign up to set email alerts
|

The role of conspicuity in preventing bicycle crashes involving a motor vehicle

Abstract: Background: Bicycle use, despite its proven health and other benefits, is rarely part of everyday travel for many people due to the perceived risk of injury from collision crashes. This article investigated the role of physical vs. attention conspicuity in preventing bicycle crashes involving a motor vehicle in New Zealand. Methods: The Taupo Bicycle Study involved 2590 adult cyclists recruited in 2006 (43.1% response rate) and followed for bicycle crash outcomes through linkage to four national databases. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Although such clothing appears to increase visibility in artificial test situations (Kwan and Mapstone, 2004), a systematic review did not identify 'real world' evidence that the use of 'conspicuity aids' is associated with reduced injury risk (Kwan and Mapstone, 2009). Subsequent work has not provided clear evidence of benefit (Miller, 2014, Tin Tin et al, 2014, Walker et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Although such clothing appears to increase visibility in artificial test situations (Kwan and Mapstone, 2004), a systematic review did not identify 'real world' evidence that the use of 'conspicuity aids' is associated with reduced injury risk (Kwan and Mapstone, 2009). Subsequent work has not provided clear evidence of benefit (Miller, 2014, Tin Tin et al, 2014, Walker et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…pointed out that it is unclear the effect of the use of high-visibility clothing on cyclist safety (Kwan and Mapstone, 2006;Miller et al, 2017;Tin Tin et al, 2014). While the use highvisibility clothing for cyclist has the potential to improve recognition and detection in laboratorybased and road-based simulation trials (Kwan and Mapstone, 2006), according to Miller et al (2017), high-visibility clothing may not be effective in promoting cycling safety when used in the absence of other bicycle crash prevention measures such as lower motor vehicle speeds.…”
Section: Discussionmentioning
confidence: 99%
“…One systematic review analyzing 42 trials assessing the effect of visibility aids on drivers' responses revealed that while visibility aids may have the potential to increase visibility and improve drivers' responses in detection and recognition, the effect of their use on cyclist safety remains to be determined (Kwan and Mapstone, 2006). The findings of recent studies suggest that the safety effect of high-visibility bicycle clothing is not consistent (Lahrmann et al, 2017;Miller et al, 2017;Tin Tin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclists are aware of this and tend to look out for motorised vehicles. Drivers are less aware of cyclists, partly because they pose less risk than other motorised vehicles, and also because they are encountered less frequently and therefore may not be prominent in the driver's expectations about what they are likely to see (Tin Tin et al, 2014). A similar reduced awareness occurs for motorcyclists.…”
Section: Road User's Responsibilitiesmentioning
confidence: 99%